CAPITAL STRUCTURE AND FINANCIAL PERFORMANCE: EVIDENCE FROM NIGERIAN LISTED INDIGENOUS OIL AND GAS FIRMS - Abubakar Ajide ARIKEWUYO; Abdullahi Adio Babatunde; Yusuf Olamilekan Quadri (Malete Journal of Accounting and Finance)
The combination of equity capital and debt capital forms the capital structure of an enterprise which in achieving firms’ objective is the utmost aspect of managerial and financial decisions. It has the ability of manipulating the operating, non-financial and financial performances of a firm as well as risk exposure due to returns payable to the provider of capital in the form of interest and dividend. Hence, this study takes a look at how the capital structure impacts on the financial performance of listed indigenous oil and gas firms in Nigeria. The study adopted an ex-post facto research design and data was extracted from annual reports of the eight (8) sampled firms for periods of 2009 to 2018. The data was analyzed using panel data regression technique to examine the extent of the impact of the independent variables on the dependent variables. The study revealed that at 0.05 significant level, Short-term Debt (STD) and Equity (EQ) have a positive and significant impact on the financial performance of listed oil and gas firms in Nigeria in terms of Return on Assets (ROA) and Return on Equity (ROE) while Long-term Debt (LTD) had a negative significant impact on the financial performance in terms of Return on Assets (ROA) and Return on Equity (ROE) of listed indigenous oil and gas firms in Nigeria. Thus, the study concluded that capital structure has a positive impact on the financial performance of listed indigenous oil and gas firms in Nigeria. Therefore the study recommended that indigenous oil and gas firms in Nigeria should adopt a short term capital for short term financing to avoid the problem of over-capitalization, which will, in turn, lead to drop in the financial performance and a long term debt should be used to implement the capital projects to avoid the problem of over-trading by oil and gas firms in Nigeria because long term debt contribute less to financial performance.